1998
DOI: 10.2172/665911
|View full text |Cite
|
Sign up to set email alerts
|

Plutonium(IV) precipitates formed in alkaline media in the presence of various anions

Abstract: SummaryThis investigation was undertaken to obtain new data on the composition and properties of . plutonium(IV) compounds formed under diverse conditions in strongly alkaline media in the presence of various anions. Such information is important to understand P u o behavior and the forms of its existence in the alkaline sludges of Hanford Site radioactive waste tanks. The knowledge then may be applied to assess plutonium disposition in the 'storage, retrieval, and treatment of Hanford Site tank wastes with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 6 publications
2
13
0
Order By: Relevance
“…Overall, the XRD measurements in the present study, the published laboratory findings [12][13][14][15][16][17], and theoretical predictions based on the solubility products of the nascent PuO 2 ·xH 2 O and fully crystalline PuO 2 as interpreted by work of Schindler [18] concur that the PuO 2 ·xH 2 O birth particles produced by precipitation from solution are about 2-5 nm in diameter.…”
Section: Effect Of Aging On the Properties Of Puo 2 ·Xh 2 O Prepared supporting
confidence: 82%
See 1 more Smart Citation
“…Overall, the XRD measurements in the present study, the published laboratory findings [12][13][14][15][16][17], and theoretical predictions based on the solubility products of the nascent PuO 2 ·xH 2 O and fully crystalline PuO 2 as interpreted by work of Schindler [18] concur that the PuO 2 ·xH 2 O birth particles produced by precipitation from solution are about 2-5 nm in diameter.…”
Section: Effect Of Aging On the Properties Of Puo 2 ·Xh 2 O Prepared supporting
confidence: 82%
“…The PuO 2 ·xH 2 O particle size formed by plutonium nitrate salt precipitation by alkaline and neutral solution has been measured in several previous studies [12][13][14][15][16][17]. Work done in the Manhattan Project showed that PuO 2 ·xH 2 O solids precipitated from acidic Pu(IV) nitrate solution with excess ammonium hydroxide solution and then air-dried at 70 • C had 3-nm particle size as measured by XRD reflection line broadening [12].…”
Section: Effect Of Aging On the Properties Of Puo 2 ·Xh 2 O Prepared mentioning
confidence: 99%
“…However, precipitated plutonium silicate deposits might occur (Section 5.3.1 and 6.2 of Delegard and Jones (2015)). Increased dehydration also occurs for PuO 2 •xH 2 O as hydrothermal aging temperature increases at least over the range of 10 to 200° C (Krot et al 1998c;Yusov et al 2000a). The differential dissolution of plutonium and solids of the absorber elements from such thermally aged materials is not known, however, except to the extent that tank wastes also have been thermally aged by decades-long storage at temperatures that sometimes have exceeded boiling.…”
Section: Pe2 -Nitricmentioning
confidence: 99%
“…The separation of plutonium from iron-bearing solids (amorphous ferric hydroxide and goethite, FeOOH) by leaching with alkaline EDTA solutions was studied by Krot et al (1998c). They examined the physical characteristics of the bulk precipitates and the susceptibilities of the precipitated products to leaching by use of 0.1 M EDTA in 1 M NaOH containing 5 M NaNO 3 .…”
Section: Op2 -Wtp Feed Holds Unexpected Organic Complexantmentioning
confidence: 99%
“…Anions (Krot et al 1998); (Fedoseev et al 1998); (Peretrukin et al 1998). (Vail 1997b), which documents the evaluation of transferring waste from DST C-106 to DST AY-102, provides a good review of the chemical processes that ensure criticality safety in waste disturbing operations.…”
Section: Plutonium(iv Precipitates Formed In Alkaline Media In the Prmentioning
confidence: 99%